Register to reply

Simple solution?

by eskil
Tags: simple, solution
Share this thread:
eskil
#1
Aug20-08, 12:13 PM
P: 4
just looking for a quick solution for my equation, seems like my head is just working the wrong way coz I know it's not a hard one:

a2 + a2 = (a + 1)2

a = ?
Phys.Org News Partner Science news on Phys.org
Climate change increases risk of crop slowdown in next 20 years
Researcher part of team studying ways to better predict intensity of hurricanes
New molecule puts scientists a step closer to understanding hydrogen storage
rock.freak667
#2
Aug20-08, 12:29 PM
HW Helper
P: 6,207
a2+a2=2a2
expand the right side and then simplify.
eskil
#3
Aug20-08, 12:37 PM
P: 4
i don't believe that (a + 1)(a + 1) is 2a2
shouldn't that give a2 + 2a +1 ??

NoMoreExams
#4
Aug20-08, 12:41 PM
P: 626
Simple solution?

[tex] a^{2} + a^{2} = (a+1)^{2} [/tex] simplifies to [tex] a^{2} + a^{2} = a^{2} + 2a + 1 [/tex] which when you move everything over to one side becomes [tex] a^{2} - 2a - 1 = 0[/tex] which is easy enough to solve. Not sure how rock.freak got what he did.
snipez90
#5
Aug20-08, 01:12 PM
P: 1,105
Quote Quote by rock.freak667 View Post
a2+a2=2a2
expand the right side and then simplify.
I'm sure he was simplifying the left side (how much simpler can it be?). Then he said expand the RHS and rearrange to solve.
eskil
#6
Aug20-08, 01:22 PM
P: 4
solved it now

a2 + a2 = a2 + 2a + 1

simplified it to a quadraticequation

0 = -a2 + 2a + 1

a1 = 1 + sq.root of 2
a2 = 1 - sq.root of 2

a2 is negative therefore a1 is the right answer

which gives a = 2,41
NoMoreExams
#7
Aug20-08, 01:29 PM
P: 626
Quote Quote by eskil View Post
solved it now

a2 + a2 = a2 + 2a + 1

simplified it to a quadraticequation

0 = -a2 + 2a + 1

a1 = 1 + sq.root of 2
a2 = 1 - sq.root of 2

a2 is negative therefore a1 is the right answer

which gives a = 2,41
Why can't a be negative?

On the LHS you had [tex] a^{2} + a^{2} = (1 - \sqrt{2})^{2} + (1 - \sqrt{2})^{2} = 1 - 2 \sqrt{2} + 2 + 1 - 2 \sqrt{2} + 2 = 6 - 4 \sqrt{2} [/tex]

However on the RHS you had [tex] (a+1)^{2} = (1 - \sqrt{2} + 1)^{2} = (2 - \sqrt{2})^{2} = 4 - 4 \sqrt{2} + 2 = 6 - 4 \sqrt{2} [/tex]

Note also that the "simpler" way to do this would be to rewrite it as

[tex] 2a^{2} = (a+1)^{2} \Rightarrow \sqrt{2} |a| = |a + 1| [/tex] and examine the appropriate regions to get rid of | |.
eskil
#8
Aug20-08, 03:51 PM
P: 4
The reason why it cannot be negative is that the origin of the problem was to determine the length of all sides of a likesided triangle thus can't be negative.

I still think that using the quadratic equation is the simplest way of solving it.


Register to reply

Related Discussions
Solution of a simple Differential Equation Differential Equations 5
Solution to Simple Matrix Equation General Math 1
Simple solution of FLT? Linear & Abstract Algebra 28
Need solution tto simple problem Introductory Physics Homework 4
Simple harmonic oscillator general solution Classical Physics 5